Strains of Achromobacter xylosoxidans from clinical material. - Holmes, B (1977)
Eleven strains of Achromobacter xylosoxidans have been received from among 1106 strains of Gram-negative, non-fermentative bacteria submitted to the National Collection of Type Cultures for computer-assisted identification since 1 January 1972. The strains showed resistance to a wide range of antimicrobial agents and five of the isolates possibly played a pathogenic role. The biochemical characteristics of these 11 strains were compared with those of three culture collection strains.